TEACHING WRITING SKILL IN IMPROVING THE STUDENTS’ WRITING SKILLS BY USING GENERATIVE LEARNING MODEL - Said, Saiful (Fakultas Keguruan dan Ilmu Pendidikan, 2014)
This research aims to find out the improving the students’ writing skills by using Generative Learning. Two cycles had been conducted, where each cycle consisted of four meetings. It employed writing test as instrument. A number of subjects of the research were 20 students in class XII IPA. The researcher conducted a diagnostic test before implementation to know the students’ writing skills. The results of the student's writing test in cycle 1 and cycle 2 had increased in different scores.  There was increasing by students at the end action of second cycle. The research findings indicated that use of Generative Learning Model could increase the students’ writing skills. The mean scores of narrative text and recount text in diagnostic test was 59 become 67.83 in cycle 1, and after revision in the cycle 2 the mean score in cycle 2 was 76.49 by implemented of narrative text and recount text. Therefore the improvement of narrative text and recount text  in cycle 1 to narrative text and recount text in cycle 2 was 12.83%. It means that the teacher could achieved the target become 70.